HUMANITARIAN LOGISTICS AND STRATEGIC MANAGEMENT IN DISASTER SCENARIOS: CHALLENGES, TECHNOLOGICAL SOLUTIONS, AND OPTIMIZATION MODELS (Interdisciplinary Studies Journal, 2025)
Humanitarian logistics has gained global prominence due to the increase in natural disasters, pandemics, and crises that require rapid responses to save lives and reduce socioeconomic impacts. Post-disaster operations, such as infrastructure damage and resource shortages, demand well-structured strategies to avoid critical delays. The COVID-19 pandemic exposed logistical flaws, reinforcing the need for studies that integrate theory and practice. This study explores post-disaster operational challenges and innovative strategies to improve supply chain management in critical contexts. It focuses on emerging technologies, mathematical models, and multisectoral cooperation. Among the objectives are identifying challenges in disaster logistics, analyzing the impact of technological innovations, and proposing strategies to increase efficiency and resilience. The results show that optimization models reduced delivery time by 35% in earthquake scenarios. Drones were four times more effective in remote areas. During COVID-19, collaboration between governments and NGOs expanded vaccination in vulnerable regions. It is concluded that the effectiveness of humanitarian logistics depends on technology, institutional collaboration, and predictive models. Investments in adaptive infrastructure, capacity building, and interdisciplinary research are crucial for building resilient systems.
Keywords: Humanitarian Logistics; Disaster Management; Emerging Technologies; Operational Resilience; Multisectoral Collaboration